2009
DOI: 10.1353/dem.0.0038
|View full text |Cite
|
Sign up to set email alerts
|

Dual citizenship rights: do they make more and richer citizens?

Abstract: In the 1990s, Colombia, the Dominican Republic, Ecuador, Costa Rica, and Brazil passed dual citizenship laws granting their expatriates the right to naturalize in the receiving country without losing their nationality of origin. I estimate the effects of these new laws on naturalization rates and labor market outcomes in the United States. Based on data from the 1990 and 2000 U.S. censuses, I find that immigrants recently granted dual nationality rights are more likely to naturalize relative to immigrants from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 26 publications
4
70
1
3
Order By: Relevance
“…In other words, the positive effect for Asians may be unique to certain countries of origin, not generally representative of the Asian population in the U.S. On the other hand, the effects for Hispanics are strongly affected by the cases of Mexico and the Dominican Republic, both of which instituted dual citizenship relatively recently. Both Jones-Correa (2001b) and Mazzolari (2009) show that effects of dual citizenship on naturalization are strongest for recent adopters. Possibly, then, what we have found is not a general “Hispanic” effect but an effect of recent adoption that might be found for immigrants from non-Hispanic countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the positive effect for Asians may be unique to certain countries of origin, not generally representative of the Asian population in the U.S. On the other hand, the effects for Hispanics are strongly affected by the cases of Mexico and the Dominican Republic, both of which instituted dual citizenship relatively recently. Both Jones-Correa (2001b) and Mazzolari (2009) show that effects of dual citizenship on naturalization are strongest for recent adopters. Possibly, then, what we have found is not a general “Hispanic” effect but an effect of recent adoption that might be found for immigrants from non-Hispanic countries.…”
Section: Resultsmentioning
confidence: 99%
“…To the extent that naturalization is an instrumental decision geared to position the individual with respect to state-provided social services, a restrictive policy environment may increase the incentive to become a citizen and also motivate immigrants to naturalize in order to protect, defend and assert their right to belong (Borjas 2002, Mazzolari 2009). One recent study (Van Hook et al 2006) shows that the policy environment toward immigrants at the state level – including specific policies that can restrict public assistance to non-citizens as well as broad measures of public attitudes – influence naturalization.…”
Section: Collective Effects On Immigrant Naturalizationmentioning
confidence: 99%
“…Second, are naturalised immigrants with dual citizenship less 'rooted'? The literature tentatively suggests that immigrants with dual citizenship may be less emotionally and politically attached to their new homelands than mono-national immigrants -but they tend to do better economically (Staton, Jackson, and Canache 2007;Mazzolari 2009;Mügge 2012;Yanasmayan 2015).…”
Section: Existing Approaches To the Study Of Dual Citizenshipmentioning
confidence: 99%
“…See, for example,Chiswick (1978);Bevelander (2000);Bratsberg, Ragan and Nasir (2002);Bevelander and DeVoretz (2008);Mazzolari (2009); Steinhardt (2012); OECD (2011);Dancygier and Laitin (2014). For Switzerland specifically one study found that at least among immigrants from non-OECD countries, naturalized immigrants have better labour market outcomes compared to non-naturalized immigrants(Steinhardt and Wedemeier 2012).…”
mentioning
confidence: 99%